2021
DOI: 10.1126/sciadv.abg5686
|View full text |Cite
|
Sign up to set email alerts
|

Portable air-fed cold atmospheric plasma device for postsurgical cancer treatment

Abstract: Surgery represents the major option for treating most solid tumors. Despite continuous improvements in surgical techniques, cancer recurrence after surgical resection remains the most common cause of treatment failure. Here, we report cold atmospheric plasma (CAP)-mediated postsurgical cancer treatment, using a portable air-fed CAP (aCAP) device. The aCAP device we developed uses the local ambient air as the source gas to generate cold plasma discharge with only joule energy level electrical input, thus provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 36 publications
(44 reference statements)
1
37
0
Order By: Relevance
“…[ 109 , 110 ] Recently, our group and others have demonstrated that CAP can be applied similarly to modulate the effects of immunotherapies for several applications in biomedicine. [ 100 , 111 , 112 ] Figure 6 illustrates how CAP‐based treatments can promote dendritic cell (DC) maturation in the lymph node, where DCs can present major histocompatibility complex‐peptide epitopes to T cells during primary immunization. The subsequent T cell‐mediated immune response can be augmented further via the administration of immune checkpoint inhibitors, resulting in enhanced local and systemic antiviral immunity.…”
Section: Cap‐enhanced Immunotherapy For Covid‐19 Patientsmentioning
confidence: 99%
“…[ 109 , 110 ] Recently, our group and others have demonstrated that CAP can be applied similarly to modulate the effects of immunotherapies for several applications in biomedicine. [ 100 , 111 , 112 ] Figure 6 illustrates how CAP‐based treatments can promote dendritic cell (DC) maturation in the lymph node, where DCs can present major histocompatibility complex‐peptide epitopes to T cells during primary immunization. The subsequent T cell‐mediated immune response can be augmented further via the administration of immune checkpoint inhibitors, resulting in enhanced local and systemic antiviral immunity.…”
Section: Cap‐enhanced Immunotherapy For Covid‐19 Patientsmentioning
confidence: 99%
“…Cold atmospheric pressure plasmas (CAPPs) have been successfully applied in biomedicine, [1][2][3] energy conversion, [4][5][6] agriculture, [7,8] insulation materials processing, [9,10] and some emerging industrial applications. [11,12] Plasma activated water (PAW), derived from the interaction between CAPPs and liquids (e.g., water or solutions), is a green prospective solution for a wide range of biological applications, from water purification to biomedicine.…”
mentioning
confidence: 99%
“… 131 The second study also observed hallmarks of ICD induction in gas plasma‐treated 4T1 cells in vitro, such as CRT exposure and enhanced expression of the DC maturation markers CD80 and CD86 in a plasma treatment time‐dependent fashion. 196 In vivo, tumours were grown to 500mm 2 before being surgically removed. The surgical margin was exposed to gas plasma or left untreated, and the tumour relapse growth and animal survival were significantly improved in gas plasma‐treated animals.…”
Section: Plasma Breast Cancer Treatment and Mechanism Of Actionmentioning
confidence: 99%